Response to “The Reality of Pervasive Transcription” - van Bakel, Harm; Nislow, Corey; Blencowe, Benjamin J.; Hughes, Timothy R. (PLoS biology, 2011)
[...]we demonstrate that conclusions very similar to those of our original study are reached with a dataset with far greater read depth, obtained by strand-specific sequencing of rRNA-depleted total RNA from a single cell type. [...]the mechanisms that control the positions of initiation and termination of Pol II transcription, as well as RNA processing, are imperfect, such that low-level background transcripts from both physiologically relevant and non-canonical sites arise [4]-[6].